Becoming octopus: Indigenous ways of knowing and green leadership - Rebecca Pointer; Darlene Miller (University of Johannesburg, 2024)
On 30 June 2014 we (a small group of academic women) opened our first Green Leadership School, an experiment in decolonising the classroom, exploring indigenous environmental knowledge, and creating a space of healing and love. This paper documents the process of healing and rejuvenating the lives of activists, government officials, trade unionists, and university students. Similar to the concept of Deleuze and Guattari's (2004) "becoming animal" and "becoming wolf", we represented the school as  "becoming octopus" - a creature with green blood (becoming green), the highest brain-to-body ratio of any invertebrate, many slithering arms to twist and escape oppression and slide away from toxic spaces, and three hearts for the three-hearted practices of love, bodily integration, and mind-spirit awareness. Therefore, the pedagogical experiment focused on transmutation - connecting with the environment through merging human with animal, ritual and magic, gardening, yoga, storytelling, music, and art alongside more conventional lectures such as understanding climate change through South African vernaculars, 'land grabs' in Africa, pollution in South Durban, and environmental communication. Damaged by apartheid and post-apartheid wounds and worldwide ruptures in the socius - the participants experienced psychic healing. This paper discusses the role of joyful pedagogies in decolonising education.